Application of Ultrasonic Methods in Super POD Thickness Measurement Examination - Wardhani, Rachmasari Pramita (PT. Riset Press International, 2024)
NDT is a scientific field of engineering that includes testing and inspection of materials and equipment which is useful for evaluating a condition, finding deficiencies and defects, and also extending the useful life of the infrastructure used. The main difference between non-destructive testing and other forms of material evaluation is that non-destructive testing allows evaluation or inspection of parts on site without having to permanently modify or damage the part. In maintaining the credibility of the company's services, the company adopting NDT/NDE testing techniques in carrying out regular inspections or checks on the tools used, one of which is the application of the ultrasonic method on the Super POD (Programmable Optimum Density). Based on this background, the author chose the theme of the study to write a scientific paper entitled “Application of Ultrasonic Methods in Super POD Thickness Measurement Examination”. The SBF-624 Super POD (programmable optimum density, POD) is a trailer-mounted fracturing service blender that can blend and pump up to 120 barrels per minute of fracturing slurry. The Super POD computers precisely control the solid-to-liquid ratio of the prop pant at design values in either ramp or stair-step mode. The results of observations of objects that have been inspected using the ultrasonic method, namely measuring the thickness of the Super POD SBF 624, from the good results without any defects being detected, and cleaned in surface condition so it can be said that the machine has shown good effective results and can meet the standards for using tools for the company.